2021
DOI: 10.3390/socsci10010016
|View full text |Cite
|
Sign up to set email alerts
|

Stonewalling in the Brick City: Perceptions of and Experiences with Seeking Police Assistance among LGBTQ Citizens

Abstract: Extant research has documented police interactions between racial and ethnic minority populations, including negative perceptions of and experiences with the police; police corruption and misconduct; and the deleterious effects of negative relationships with the police, such as reduced legitimacy and mistrust. Comparatively, exchanges between lesbian, gay, bisexual, trans, and queer (LGBTQ) populations and the police have received limited attention. This is despite work suggesting that LGBTQ citizens face an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…The historical (and continued) pattern of discriminatory and homophobic interactions with police officers has undermined LGBTQ perceptions of police. Although limited, the extant data on LGBTQ perceptions of police officers suggests generally impaired trust, perceived fairness, and quality of interactions (Finneran & Stephenson, 2013; Miles‐Johnson, 2015; Owen et al, 2018; Shields, 2021), with the exception of one study (to our knowledge) that reported generally positive perceptions of police among attendees at a pride event in Atlanta (Gillespie, 2008). For example, Owen et al (2018) conducted a study that found poorer perceptions of police across several metrics, when compared with their heterosexual counterparts—persisting even when race, income, rurality of residence, and personal history of police interactions were controlled for.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The historical (and continued) pattern of discriminatory and homophobic interactions with police officers has undermined LGBTQ perceptions of police. Although limited, the extant data on LGBTQ perceptions of police officers suggests generally impaired trust, perceived fairness, and quality of interactions (Finneran & Stephenson, 2013; Miles‐Johnson, 2015; Owen et al, 2018; Shields, 2021), with the exception of one study (to our knowledge) that reported generally positive perceptions of police among attendees at a pride event in Atlanta (Gillespie, 2008). For example, Owen et al (2018) conducted a study that found poorer perceptions of police across several metrics, when compared with their heterosexual counterparts—persisting even when race, income, rurality of residence, and personal history of police interactions were controlled for.…”
Section: Introductionmentioning
confidence: 81%
“…For example, Owen et al (2018) conducted a study that found poorer perceptions of police across several metrics, when compared with their heterosexual counterparts—persisting even when race, income, rurality of residence, and personal history of police interactions were controlled for. Indeed, a more recent study found that many LGBTQ remain reluctant to seek assistance from police, hold generally low opinions of police, and have experienced negative encounters with police including instances of misconduct and harassment (Shields, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consider hiring a third-party mediator to handle code of conduct violations. Do not equate police presence with safety, as queer and trans communities are often the subjects of police harassment ( 43 ). In addition, monitor social media and conference hashtags for harassment of specific conference attendees or marginalized groups.…”
Section: During the Conferencementioning
confidence: 99%
“…Within the last decade, there has been more research attention on how sexual and gender minorities (i.e., individuals who do not identify with the gender they were assigned at birth) perceive the police (Dario et al, 2020; Nadal et al, 2015; Owen et al, 2018; Shields, 2021). Though research in this area is gaining more interest, sexual and especially gender minorities’ perceptions of the police remain relatively unexplored in the literature.…”
Section: Perceptions Of Policementioning
confidence: 99%